PENGARUH PENERAPAN STRATEGI SEPAK BOLA VERBAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 28 PADANG - Wahyuni, Sri; Delsi K, Delsi K; sovia, Anny (Pendidikan Matematika, 2014)
ABSTRACTThis research was designed for determining whether the mathematics conceptual understanding of the students taught by using Verbal Football Strategy better than that of students taught by using conventional learning in class VIII of SMPN 28 Padang. This was an experimental research which used random toward the subject design. The data was collected by using a posttest on mathematics conceptual understanding. The result of hypothesis test showed that P-value (0,0000) was smaller than Î± = 0,05 indicating that the hypothesis was accepted. Thus, it was concluded that the mathematics conceptual understanding of the students taught by using Verbal Football Strategy was better than that of students taught by using conventional learning in class VIII of SMPN 28 Padang.